Quality of Education Systems: Evaluation Models - Fernández-Alonso, Rubén (2019)
The Psychometric Research Group of the University of Oviedo participated in different presentations and workshops organized within the framework of the II International Congress of Psychological Evaluation held in November 2018 at the San Ignacio De Loyola University (Lima, Peru). This work gathers part of those contributions. Specifically, the aim of this paper is to present the mathematical models and methodological procedures available for the analysis of data in the evaluation of educational systems. The design, execution and dissemination of the results of an evaluation program of the education system is a complex task that poses a challenge in different areas, among which data analysis stands out. These programs have two main purposes: to know and describe the level of knowledge and skills of the student population and to identify and analyze the context and process factors associated with educational outcomes. In order to fulfil both purposes, the evaluation of education systems has been provided with unique and specific methodological solutions. Three of them are presented in this paper. Two are aimed at expressing learning outcomes: plausible values and cut-off methods, while the last focuses on analyzing the relationship between school factors and outcomes.